2018
DOI: 10.1074/jbc.ra118.002780
|View full text |Cite
|
Sign up to set email alerts
|

Effects of phosphatidylcholine membrane fluidity on the conformation and aggregation of N-terminally acetylated α-synuclein

Abstract: Membrane association of α-synuclein (α-syn), a neuronal protein associated with Parkinson's disease (PD), is involved in α-syn function and pathology. Most previous studies on α-syn-membrane interactions have not used the physiologically relevant N-terminally acetylated (-acetyl) α-syn form nor the most naturally abundant cellular lipid, phosphatidylcholine (PC). Here, we report on how PC membrane fluidity affects the conformation and aggregation propensity of N-acetyl α-syn. It is well established that upon m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
77
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 67 publications
(94 reference statements)
6
77
0
Order By: Relevance
“…This suggests that a tighter and more ordered packing of lipids has a negative impact on the α -Syn bilayer interaction, although the presence of net negative charge is a stronger determinant in the current setup. Our findings are consistent with recent studies reporting that cholesterol has negative effect on α -Syn binding 25 , and with reports finding that bilayer fluidity is an important driver for binding alongside charge 4,42 .…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…This suggests that a tighter and more ordered packing of lipids has a negative impact on the α -Syn bilayer interaction, although the presence of net negative charge is a stronger determinant in the current setup. Our findings are consistent with recent studies reporting that cholesterol has negative effect on α -Syn binding 25 , and with reports finding that bilayer fluidity is an important driver for binding alongside charge 4,42 .…”
Section: Introductionsupporting
confidence: 93%
“…Other reports on the effect of cholesterol on α -Syn fibrillation are conflicting. Some studies using lipid vesicles did not observe any promotion of α -Syn fibrillation by lipid vesicles containing cholesterol 25,62 , while other studies observed increased oligomerization in the presence of oxidized cholesterol metabolites 66 or increased fibrillation and deposit formation in cell cultures exposed to higher cholesterol concentrations 67 . The lipid nanodiscs used in our experiments are much smaller (see Table S1) than vesicles used in previous experiments and there is a lack of stored curvature elastic stress.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…cates that Lti30 indeed cross-links the membrane. N-terminally acetylated ␣-synuclein was found to have shortened aggregation kinetics and promoted fibril formation with gel-phase vesicles as compared with fluid membranes (37). Here, we find that Lti30 gives a ThT signal mainly at low pH with fluid membranes, indicative of fibril formation.…”
Section: Modulation Of Membrane Fluidity By Lti30mentioning
confidence: 58%
“…␣-synuclein and CTP:phosphocholine cytidylyltransferase (CCT), that are able to sense lipid-packing defects that are normally enriched in curved surfaces (37,38). Like the dehydrins, the disordered ␣-synuclein and CCT employ induced amphipathic helices that recognize the physical properties of the target membrane surfaces.…”
Section: Modulation Of Membrane Fluidity By Lti30mentioning
confidence: 99%